Hubungan Dukungan Keluarga Dengan Respon Berduka Pada Klien Kanker Di Rumah Sakit Islam Sakinah Mojokerto - Triwibowo, Heri; Frilasari, Heni (Jurnal Keperawatan Bina Sehat, 2013)
Cancer is a long period of time disease, especially can be life threaten. Cancer client who has appearance change caused from disease process and treatment program will under go a process of change that begin with denial, anger, bargaining, depression, and acceptance. Support have to be available when the client who is grieving through the mourning process. The purpose of this research was to know the correlation between the family support with grieving response to cancer client at the Sakinah Islamic Hospital Mojokerto. The research is kind of correlation analytical with cross sectional approach. Population of the research is 13 cancer client. The sample quantity taken is 9 respondents using consecutive sampling technique for a month. Collecting data use a questionnaire and were tested with Fisher’ Exact Test, with ρ = 0,008, it is means ρ < α (0,005), so H0is rejected which mean there is a correlation between the family support with grieving response to cancer client at the Sakinah Islamic Hospital Mojokerto. A good family support will help the respondents use their coping mechanism to the best grieving response. Lack of the support can cause to difficult in successful resolution of grief that the respondent does not end up in the acceptance phase.Keywords: Family Support, Grieving Response, Cancer Client